Microeconomics - Perloff, Jeffrey M. (Pearson Education Limited, 2024)
With a focus on illustrating that economic theory has practical and problem-solving uses, Microeconomics introduces concepts, as well as tools and their applications to students. This textbook focuses on modern theories such as industrial organizational theories, transaction theory, game theory, and informational theory, to help students understand and analyze real markets. Each chapter has real-world examples which explain basic theories and their relevance in actual situations and encourage students to explore how microeconomics can be relevant to disciplines like policymaking and law. A step-by-step problem-based learning approach is present across chapters, and this provides guidance on how to apply microeconomic theory when solving problems given at the end of each chapter.